The State of Cities Climate Finance : Part 2. The Enabling Conditions for Mobilizing Urban Climate Finance - World Bank (World Bank, Washington, DC, 2021)
The Enabling Conditions for Urban Climate Finance Part 2 is a contribution of the World Bank to the State of Cities Climate Finance Report 2021. Part 2 analyzes enabling frameworks and presents solutions for mobilizing urban climate finance at scale to transition cities to low-carbon, climate-resilient development pathways. It seeks to provide a common level of understanding of the terminologies, knowledge, and themes used by climate policy and climate finance practitioners, city-level urban planners, and municipal finance officials. It presents innovative and critical concepts on the roles and agency of city governments in climate action; the enabling conditions at the country, city, and climate transaction level; concrete practical examples, solutions and approaches and key recommendations for local, national, and international officials to mobilize urban climate finance at scale. The entire State of Cities Climate Finance Report, including the Executive Summary, is available here: https://www.citiesclimatefinance.org/2021/06/2021-state-of-cities-climate-finance/ .